Circulating Th1 and Th2 cytokines in patients with hepatitis C virus infection. Issue 4 (1998) - Fan, X. G.; Liu, W. E.; Li, C. Z.; Wang, Z. C.; Luo, L. X.; Tan, D. M.; Hu, G. L.; Zhang, Z.
Abstract : The imbalance of T-helper (Th) lymphocyte cytokine production may play an important role in immunopathogenes is of persistent hepatitis C virus (HCV) infection. To know whether an imbalance between Th1 and Th2 cytokines is present in chronic HCV infection, serum levels of Th1 cytokines, interferon gamma (IFN-γ ) and interleukin (IL)-2, and Th2 cytokines, IL-4 and IL-10, were measured using enzyme - linked immunosorbent as say in this study. Eighteen individuals with chronic HCV infection, 11 healthy subjects as normal controls and 10 chronic HBV infected patients as disease controls were observed. The results showed that the leve ls of Th2 cytokines (IL-4 and IL-10) were significantly increased inchronic HCV infected patients compared with normal controls (IL-4: 30.49 ± 17.55 vs . 14.94 ± 13.73, pg/ml, p < 0.025 ; IL-10: 50.30 ± 19.59 vs. 17.87 ± 9.49, pg/ml, p < 0.001 ). Similarly, the levels of Th1 cytokine, IL-2, was also elevated in individuals with chronic HCV infection when compared with normal controls (IL-2: 118.53 ± 95.23 vs . 61.57 ± 28.70, pg/ml, p < 0.05 ). However, Th1 cytokine IFN-γ level was not significantly changed during HCV infection (IFN-γ: 28.09 ± 15.65 vs . 24.10 ± 15.61, pg/ml, p > 0.05 ). Further more, the elevated levels of Th2 cytokines are greater than Th1 cytokines in HCV infection. Thus, the study indicates that an enhanced Th2 responses are present during chronic HCV infection, which may partly be responsible for the persistence of HCV infection.